TRIASSIC SILICEOUS FORMATION IN THE KHOR RIVER BASIN (CENTRAL SIKHOTE ALIN) - Volokhin Yu.G.; Mikhailik E.V.; Burii G.I. (My University, 1999)
In the Khor River middle courses, the Triassic siliceous formation about 430 m thick represents the transgressive-regressive megacyclothem composed of carbonate-siliceous deposits bearing conodonts of the middle Anisian to late Norian (Rhaetian ?) period of time. The decreased thickness of upper Ladinian (24 m) and Carnian (27 m) beds is associated with cryptic intraformational hiatuses that is established within the siliceous sequence exposed along the Lyamfana Creek in close proximity to the Khankai massif. The hiatuses are correlated with events of erosion that affected terrigenous shelf deposits of the South Primor'e, Arsen'ev, and Alchan zones. The bed sequence within the carbonate-siliceous megacyclothem corresponds to cycles of the global eustatic changes of sea level during the Triassic. The thick carbonate deposits of the Sikhote Alin basin accumulated at the time of maximum sea-level stand (Carnian-middle Norian), when there was the sea transgression over the Khankai land. Silica accumulation rates during the Anisian (2.8-3.0 g/cm(2)/1000 years) and Ladinian (2.7-3.1 g/cm(2)/1000 years) were similar to current parameters characterizing the biogenic silica precipitation in the Far East marginal seas, some inner sea basins (e.g., the Sea of Azov), and coastal upwelling zones (Peru-Chile region). They were one order of magnitude higher than rates of pelagic silica accumulation in the northern and equatorial Pacific. The much slower silica accumulation during the Carnian (0.33 g/cm(2)/1000 years) and Norian (0.62-0.63 g/cm(2)/1000 years) was compensated by carbonate sedimentation that seems to be a response to migration of habitat areas of siliceous and calcareous plankton during the transgressive epochs interrelated with the eustatic sea-level changes.
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая